Área de vida e territorialidade do lobo-guará (Chrysocyon brachyurus ILLIGER, 1811) no Parque Nacional da Serra da Canastra, Minas Gerais, Brasil - Luiz Filipe de Abreu Rosa Alves Bento (2013)
Radio telemetry collars have been used to study the biology of wild animals since 1959, allowing researchers to obtain valuable information about the ecology and behavior of wild populations. To better understand the spatial distribution of maned wolves (Chrysocyon brachyurus) in the Parque Nacional da Serra da Canastra, Minas Gerais, Brazil, methods of VHF telemetry and GPS telemetry was used to check if areas not previously sampled by VHF technology can be sampled by GPS collar. The use of GPS telemetry locations had an average per month of 20 times more than compared to VHF telemetry, with the accuracy of the locations of 93%. Variations in the home range areas were observed due to the number of locations and how they were distributed, affecting the behavior of the smoothing factor of the estimation method of adaptive kernel home range estimator. The GPS telemetry managed to record movements lost by VHF telemetry. As the accuracy of locations obtained by GPS telemetry is high, studies of habitat utilization are more accurate and can be analyzed what kind of environment the animal used, which is not as well defined by telemetry VHF, since a higher error in locations generates doubt whether the animal is in a habitat or another.